(untitled) (Informatica, 2017)
An improved Gene Expression Programming (GEP) based on niche technology of outbreeding fusion (OFN-GEP) is proposed to overcome the insufficiency of traditional GEP in this paper. The main improvements of OFN-GEP are as follows: (1) using the population initialization strategy of gene equilibrium to ensure that all genes are evenly distributed in the coding space as far as possible; (2) introducing the outbreeding fusion mechanism into the niche technology, to eliminate the kin individuals, fuse the distantly related individuals, and promote the gene exchange between the excellent individuals from niches. To validate the superiority of the OFN-GEP, several improved GEP proposed in the related literatures and OFN-GEP are compared about function finding problems. The experimental results show that OFN-GEP can effectively restrain the premature convergence phenomenon, and promises competitive performance not only in the convergence speed but also in the quality of solution.